Exploring the Path of Digital Economy Assisting Rural Revitalization - Pu, Xinyu (Transactions on Economics, Business and Management Research, 2024)
The rural revitalization strategy is an important strategy proposed by China to solve the issues of agriculture, rural areas, and farmers. The issues of agriculture, rural areas, and farmers are of utmost importance in the work of the entire Party of China. With the continuous deepening of rural revitalization, the penetration and integration role of the digital economy is increasingly evident. The digital economy provides significant support for rural revitalization, fostering its transformation and upgrading, and promoting integrated urban-rural development, thus playing a crucial role in advancing rural revitalization. This article comprehensively studies how the digital economy can help rural revitalization, as discussed in multiple papers. This article elaborates on the process and current situation of rural revitalization, identifies the development and existing problems of digital economy in promoting rural revitalization, and explores how to further optimize the digital economy in promoting rural revitalization. This article offers suggestions and support for rural revitalization, which can promote its comprehensive development and progress, leading to shared prosperity in rural areas.